THE ROLE AND IMPORTANCE OF DATA MINDSIGHTING IN BIG DATA THEORY (Modern education and development, 2025)
The rapid expansion of big data necessitates advanced analytical approaches to extract meaningful insights. Data mindsighting, a novel concept integrating cognitive analytics, artificial intelligence (AI), and predictive modeling, plays a critical role in understanding and interpreting massive datasets. This paper explores the role and importance of data mindsighting in big data theory, its methodologies, applications, and future prospects.